The Effect of Food Addiction in Children on Obesity: A Systematic Review and Meta-Analysis Study - Murat Bektaş; Dilek Demir; Şenay Demir; İlknur Bektaş (Galenos Yayinevi, 2021)
Aim:This study aimed to analyse the effect of food addiction in children on obesity.Materials and Methods:A comprehensive literature review was conducted between January 2013 and July 2019 (Google Scholar, Pubmed, Embase/Elsevier, PsycINFO, EBSCOhost, Science Direct, BioMed Central). The word combinations "child", "adolescent", "obesity", "food addiction", "eating behaviour" and "food addiction scale for children" were used in the search process. The selected articles were examined in detail by two independent reviewers, and the methodological quality of the studies to be included in this study were evaluated using the Joanna Briggs Institute Meta-Analysis Statistical Appraisal and Review Tool (JBI-MAStARI Critical Appraisal Tool). General effect size, tests of heterogeneity, publication bias, and sensitivity analyses were performed with the random-effects model. The Comprehensive Meta-Analysis 3 software package was used for data analysis.Results:As a result of the test of heterogeneity, those studies falling within the food addiction in children sub-dimension were determined to show heterogeneous characteristics (Q=74,109, I2=83.80, p<0.01). The result of the publication bias test indicated the presence of publication bias. The overall effect size value of all studies, which was found using the random-effects model, was determined to be 0.346 [95% confidence interval (CI)], a value between the 0.152-0.539 CI. According to the results, food addiction was found to have a positive and moderate effect size on obesity when the average effect sizes within a 95% CI were considered. Accordingly, food addiction was determined to significantly affect obesity in children (p<0.05).Conclusion:In this study, food addiction in children was determined to affect the prevalence of obesity in children.